1988
DOI: 10.2514/3.59
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the transient heat transfer across periodically contacting surfaces

Abstract: This study experimentally examines the heat transfer across surfaces which contact and separate at regular intervals. The results are presented for the case of low contact pressure, moderate interface temperature, equal contact and separation times during a cycle, and identical materials on either side of the contact interface. The results are presented in two basic areas: 1) the behavior of the thermal contact resistance during the quasi-steady state; and 2) the length of time required for the temperature dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 13 publications
(5 reference statements)
4
14
0
Order By: Relevance
“…These results, which are reported by Moses, indicated that, within the accuracy of the recording device, the heat flow down the rod was one-dimensional [13][14]. Table 1 lists the characteristics of the experiment and specimens.…”
Section: Experimental Apparatussupporting
confidence: 65%
See 2 more Smart Citations
“…These results, which are reported by Moses, indicated that, within the accuracy of the recording device, the heat flow down the rod was one-dimensional [13][14]. Table 1 lists the characteristics of the experiment and specimens.…”
Section: Experimental Apparatussupporting
confidence: 65%
“…We consider the actual data taken from a contact conductance experiment conducted by Moses [13][14]. The experimental apparatus, consists of two test cylinders-each held at one end in a thermal reservoir, the supporting frame, and the associated equipment required to bring the test specimens uniformly into and out of contact.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Flach and Ozisik [17] employed the inverse heat conduction method for predicting time-dependent thermal contact conductance from temperature measurements taken within the mediums. Moses and Johnson [18] studied identical materials for the case of low constant pressure. The interface temperature was kept moderate for a short time, and the same contact and separation duration in a cycle were used.…”
Section: Introductionmentioning
confidence: 99%
“…Moses and Johnson [6] experimentally examined the problem of periodically contacting similar metal surfaces and obtained results that are comparable in both form and magnitude to those of Vick and Ozisik. Moses and Johnson [7] also experimentally examined the approach to the quasisteady-state condition for similar metallic surfaces in periodic contact, focusing on the behavior of the thermal contact conductance during the contact portion of a cycle and on the number of cycles required to reach a quasi-steady state condition. The experimentally obtained temperature distributions from Moses and Johnson also are examined by Beck as an example of a parameter and function estimation technique for the inverse heat conduction problem.…”
Section: Introductionmentioning
confidence: 99%